John Robert Procter papers - Procter, John Robert, 1844-1903.
Chiefly correspondence relating to Procter's service as chairman of the United States Civil Service Commission and to civil service reform. Includes writings, financial records, and family papers. Correspondence with Theodore Roosevelt prior to and during Roosevelt's presidency reflects their friendship as well as documenting official matters. Other correspondents include Grover Cleveland, Richard Watson Gilder, and Walter Hines Page.
Library of Congress Prints and Photographs Division.
Geologist and civil service reformer. Kentucky state geologist from 1880 to 1893 and chairman of the United States Civil Service Commission from 1893 to 1903.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Cleveland, Grover, -- 1837-1908 -- Correspondence; Gilder, Richard Watson, -- 1844-1909 -- Correspondence; Page, Walter Hines, -- 1855-1918 -- Correspondence; Roosevelt, Theodore, -- 1858-1919.; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; Proctor family; United States Civil Service Commission; Civil service -- United States; Civil service reform -- United States; Geologists; Public officials -- United States; Reformers